Prevalence of and Factors Associated with Insufficient Physical Activity Among Adolescents: Evidence from the National Nutrition Surveillance Study - Hossain, Md Mokbul; Shamim, Abu Ahmed; Hasan, Mehedi; Hanif, Abu Abdullah Mohammad; Hossaine, Moyazzam; Ullah, Mohammad Aman; Sarker, Samir Kanti; Rahman, S M Mustafizur; Mitra, Dipak Kumar; Haque, Md Emdadul; Mridha, Malay (Oxford Academic, 2022)
This article was published in the Current Developments in Nutrition by Oxford Academic [This article is published and distributed under the terms of the Oxford University Press, Standard Journals Publication Model (https://academic.oup.com/journals/pages/open_access/funder_policies/chorus/standard_publication_model)] and the definite version is available at: https://doi.org/10.1093/cdn/nzaa066_010 The Journal's website is at: https://academic.oup.com/cdn/article/4/Supplement_2/1755/5844713